Polyethylene composite material and preparation method thereof
By recycling high-density polyethylene and a variety of modified materials, using multi-stage exhaust extrusion process and phased addition method, the environmental pollution and resource waste problems of traditional plastic treatment methods are solved, and the polyethylene composite materials with high strength, high toughness and barrier properties are realized, which enhances its application value.
Patent Information
- Application Number
- CN202510255176.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-05
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-03-05
AI Technical Summary
Traditional plastic treatment methods lead to environmental pollution and waste of resources, and the existing technology is difficult to effectively recycle and reuse high-density polyethylene, resulting in insufficient performance to meet the application needs of multiple fields.
By recycling high-density polyethylene as a base material, combining maleic anhydride, polyolefin elastomer, polypropylene microfiber, modified glass fiber, silane modified montmorillonite, nanosilica and other components, the strength, toughness and barrier properties of the material are improved by using a multi-stage exhaust extrusion process and a phased addition method.
Polyethylene composite materials that achieve high strength, high toughness and good barrier properties effectively make up for the performance of recycled materials and enhance their comprehensive application value.
Smart Images

Figure CN119735880A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and particularly relates to a polyethylene composite material and a preparation method thereof. Background Art
[0002] With the rapid development of the global economy and the continuous improvement of people's living standards, the use of plastic products has exploded. As a widely used plastic material, high-density polyethylene (HDPE) plays an important role in many fields such as packaging, construction, agriculture, and automobiles. However, the traditional plastic disposal methods are mainly landfill and incineration. Landfill will occupy a large amount of land resources, and plastics are difficult to degrade naturally. Long-term presence in the soil will affect the permeability and fertility of the soil and cause damage to the ecological environment. Although incineration can reduce the volume of plastic waste, it will produce a large amount of harmful gases, posing a threat to the atmospheric environment and human health. As a thermoplastic polyethylene material with high crystallinity, HDPE has excellent chemical corrosion resistance, environmental stress cracking resistance and good mechanical properties, such as high strength and good toughness. HDPE is often used in packaging films, containers, pipes, films and injection molded products (such as bottle caps, household sundries, toys, etc.), and is also widely used in automobiles, home appliances, agricultural pipelines, cable protective layers and other fields. Due to its large production and demand, a considerable amount of waste plastic products are produced after the end of the use cycle. If these waste plastics lack effective recycling methods, they are likely to have adverse effects on the ecological environment and cause waste of resources. Recycling waste HDPE can significantly reduce the harm to the environment, reduce environmental pollution caused by landfill and incineration, and effectively save petroleum resources. Through recycling and reuse, the demand for virgin plastics can be reduced, production costs can be saved, and economic benefits can be brought to the relevant industrial chain. By compounding and modifying with other polymers, inorganic fillers or toughening agents and other materials, the mechanical properties, impact resistance and thermal stability of recycled HDPE can be enhanced, effectively making up for the shortcomings of recycled materials in performance, thereby enhancing its comprehensive application value. In summary, based on the above problems, it is extremely necessary to study a high-strength and high-toughness polyethylene composite material based on recycled high-density polyethylene. Summary of the invention
[0003] In view of the defects of the prior art, the object of the present invention is to provide a polyethylene composite material and a preparation method thereof.
[0004] The technical effect described in the present invention is achieved through the following technical scheme: a polyethylene composite material, which comprises the following components in parts by weight: 60 to 70 parts of high-density polyethylene, 0.6 to 1 parts of maleic anhydride, 6 to 10 parts of polyolefin elastomer, 3 to 5 parts of polypropylene microfibers, 4 to 6 parts of modified glass fibers, 2 to 3 parts of silane-modified montmorillonite, 1 to 2 parts of nano-silicon dioxide, 0.6 to 1 parts of zinc stearate, 0.5 to 1 parts of polyethylene wax, 0.2 to 0.3 parts of a primary antioxidant and 0.2 to 0.3 parts of an auxiliary antioxidant.
[0005] Preferably, the high-density polyethylene is prepared by washing, drying, crushing and drying recycled laundry detergent bottles.
[0006] Preferably, the primary antioxidant is any one of butylated hydroxytoluene, 2,4-di-tert-butylphenol and 2,6-di-tert-butyl-p-cresol.
[0007] Preferably, the auxiliary antioxidant is any one of didodecanediol thiodipropionate, tris(nonylphenyl)phosphite, and diphenylphosphite.
[0008] Preferably, the specific preparation steps of the silane-modified montmorillonite are as follows: A1: Add montmorillonite to deionized water, disperse it evenly by ultrasonic treatment, and obtain a montmorillonite dispersion; add hexadecyltrimethylammonium bromide to deionized water, stir and mix evenly, and obtain a 1-2wt% active agent solution; add γ-aminopropyltriethoxysilane to 90wt% ethanol solution, stir and mix evenly, adjust the pH to 4-5 with 0.1M hydrochloric acid solution, and hydrolyze at room temperature for 30 minutes to obtain a 4wt% silanol solution; A2: slowly add the active agent solution prepared in step A1 to the montmorillonite dispersion, control the temperature at 60-70°C, stir and react for 4-6 hours, wash with deionized water, and dry at 60°C for 12-24 hours to obtain organic montmorillonite; add the organic montmorillonite to the silanol solution prepared in step A1, stir and react at 50-60°C for 2-4 hours, wash with deionized water, and vacuum dry at 80°C for 12 hours to obtain silane-modified montmorillonite; Preferably, in step A1, the ratio of the amount of montmorillonite to deionized water is 1 g: 15-20 mL; Preferably, in step A2, the volume ratio of the active agent solution to the montmorillonite dispersion is 1-1.5:1; and the volume ratio of the organic montmorillonite to the silanol solution is 1 g:6-8 mL.
[0009] Preferably, the specific preparation steps of the modified glass fiber are as follows: B1: The glass fiber was completely immersed in deionized water, ultrasonically treated at 100W for 15 minutes, filtered, and dried at 60°C for 6 hours to obtain pretreated glass fiber; the pretreated glass fiber was added to concentrated nitric acid, stirred and reacted at room temperature for 2 to 4 hours. After the reaction was completed, it was washed with deionized water until neutral to obtain neutral glass fiber; B2: adding the neutral glass fiber prepared in step B1 into a 70wt% ethanol solution, soaking for 30 minutes, then repeatedly washing with deionized water for 3 times, and vacuum drying at 80°C for 12 to 24 hours to obtain modified glass fiber; Preferably, in step B1, the ratio of the amount of the pretreated glass fiber to the amount of concentrated nitric acid is 1 g: 5-6 mL; Preferably, in step B2, the ratio of the neutral glass fiber to the ethanol solution is 1 g: 5-10 mL.
[0010] Preferably, another aspect of the present invention is to provide a method for preparing a polyethylene composite material, and the specific preparation steps are as follows: S1: washing high-density polyethylene with deionized water, and vacuum drying at 80°C for 12 hours to obtain pretreated high-density polyethylene; stirring and mixing the pretreated high-density polyethylene, polyolefin elastomer, zinc stearate, polyethylene wax, primary antioxidant and auxiliary antioxidant to obtain a pretreated mixture; ultrasonically treating silane-modified montmorillonite, nano-silica and modified glass fiber to pre-disperse them in deionized water; extruding polypropylene at 200°C and stretching it to form 2-3 mm polypropylene microfibers; S2: adding the pretreated mixture prepared in step S1 into an extruder, melt blending at 190-200° C., controlling the speed to 60 rpm, mixing time 3-5 min, then slowly adding maleic anhydride, raising the temperature to 200-210° C., and reacting for 5-10 min; S3: After completing the operation in step S2, the silane-modified montmorillonite, nano-silica and modified glass fiber after ultrasonic dispersion in step S1 are added in sequence, the extrusion temperature is increased to 220° C., the rotation speed is increased to 80 rpm, and the mixing time is 8 to 10 minutes; S4: After completing the operation in step S3, slowly add the polypropylene microfiber prepared in step S1, reduce the rotation speed to 50-70 rpm, reduce the temperature to 200°C at a rate of 5°C / min, and disperse for 5-6 minutes. After dispersion, reduce the temperature to 190°C at a rate of 2°C / min, extrude, and then cool the extrudate to room temperature to obtain a polyethylene composite material; Preferably, in step S1, the stretching parameter of the polypropylene is a stretching ratio of 15 to 20; Preferably, in step S2, after the maleic anhydride grafting reaction is completed, the first exhaust is performed, the exhaust pressure is -0.08 MPa, and the time is 5 to 8 minutes; Preferably, in step S4, after the polypropylene microfibers are added and mixed, a second exhaust is performed, the exhaust pressure is -0.08 MPa, and the time is 5 to 8 minutes; Preferably, in step S4, the extrudate cooling step is firstly cooling with 40° C. water for 2 to 3 minutes, and then naturally cooling to room temperature.
[0011] The beneficial effects of the present invention are as follows: The present invention makes full use of recycled high-density polyethylene (HDPE) recovered from laundry detergent bottles as a base material, and after effectively removing volatile substances through a multi-stage exhaust extrusion process, maleic anhydride (MAH), silane-modified montmorillonite, nano-silica (SiO2), polyolefin elastomer (POE) and other components are added in stages, so as to improve the strength, toughness and barrier properties of the material through synergistic effects; at the same time, the oriented fiber-forming mechanism of polypropylene (PP) microfibers in secondary processing is utilized to further realize the high-value utilization of recycled high-density polyethylene.
[0012] The present invention performs an acid treatment on glass fiber (GF), and by introducing a hydroxyl polar group, improves the compatibility and interface bonding force between the glass fiber and the HDPE matrix. During the high-temperature extrusion process, maleic anhydride is added in stages, and the maleic anhydride first reacts with the polyolefin chain segments in the HDPE matrix to form a polyolefin chain with a polar group, thereby improving the compatibility between HDPE and the inorganic filler. Surface-treated inorganic fillers such as modified montmorillonite and nano-silica can be more evenly dispersed in the HDPE matrix to establish a relatively stable interface bond. When the modified montmorillonite and nano-silica are well dispersed inside the matrix, a multi-level nanostructure can be constructed to slow down crack initiation and expansion, and enhance barrier properties. In addition, the surface of the glass fiber treated with nitric acid is rich in hydroxyl groups (-OH), and the HDPE matrix modified with maleic anhydride introduces polar groups such as carboxylic acid groups (-COOH) through grafting reaction; the two significantly improve the compatibility of glass fiber and HDPE matrix through hydrogen bonding between hydroxyl-carboxylic acid groups and interaction between polar molecules, thereby enhancing the interfacial bonding force and intercalation effect, and promoting the formation of a stable multi-reinforced network in the composite material. At this time, the uniformly dispersed modified montmorillonite provides a "lamellar" barrier in the matrix, and cooperates with nano-silica to shape a multi-level nanostructure, significantly inhibiting crack propagation and improving the mechanical and barrier properties of the material.
[0013] In the preparation and processing process of the present invention, polyethylene wax (PE wax) and zinc stearate (ZnSt) are used as organic lubricants to maintain good thermal stability and lubrication effect at a relatively high processing temperature. On the one hand, the viscosity of the polymer melt and the friction of the extruder wall are reduced to ensure a smooth extrusion process; on the other hand, inorganic nanoparticles are helped to be fully dispersed in the high-viscosity melt to avoid agglomeration. In the secondary processing, polypropylene (PP) microfibers are used, and the advantages of being in the same olefin system as HDPE and having relatively close processing temperatures are utilized. By reasonably controlling the extrusion and subsequent stretching temperatures, polypropylene can form microfibers with high orientation and be distributed in a high-density polyethylene matrix. Polypropylene microfibers not only significantly improve the tensile strength and rigidity of the material, but also block or interfere with the crack path during crack propagation, thereby improving the fracture toughness and impact strength of the material. During the extrusion molding process, the high-density polyethylene matrix will melt again, while the polypropylene microfibers can maintain a fiber state due to the suitable melting point and partial crystalline structure; by controlling the temperature gradient, premature softening of the polypropylene is avoided, thereby finally forming a stable fiber network after cooling. Glass fiber provides the material with higher overall stiffness and strength, while polypropylene microfiber plays an important role in enhancing toughness. The combination of the two achieves a balance between high stiffness and high toughness. Both glass fiber and modified montmorillonite treated with nitric acid contain enhanced polar groups. The interaction between hydroxyl groups and polyolefin matrix can greatly improve the interfacial bonding between them and the polymer matrix. At the same time, maleic anhydride introduces carboxylic acid groups into the HDPE segment through melt grafting reaction. Its polar part not only forms physical interlocking with the non-polar HDPE main chain through intermolecular entanglement, but also chemically bonds with the polar groups of reinforcing phases such as glass fiber and montmorillonite, thereby constructing a synergistic reinforcement network at the multiphase interface and improving the overall structural stability of the composite material. In terms of improving toughness, polyolefin elastomers and high-density polyethylene belong to the same olefin system, have good compatibility at the molecular level, and are easy to form a relatively continuous elastic phase, which can absorb impact energy and relieve stress concentration. When polypropylene microfibers and glass fibers jointly enhance the stiffness of the material, the elastic phase of the polyolefin elastomer can effectively offset the embrittlement or notch problem, and combined with the crack interference effect of the microfibers / glass fibers, further improve the toughness of the material. The hierarchical synergistic structure between nanoparticles such as modified montmorillonite and nanosilica and the elastic phase of the polyolefin elastomer effectively improves the toughness of the composite material by inhibiting the tough-brittle transition through the functions of barrier and local stress dispersion. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0015] Figure 1 It is a test result diagram of impact strength determination and absorbed energy of the polyethylene composite materials prepared in Example 2 of the present invention and Comparative Examples 1 to 5; Figure 2 It is a graph showing the anti-aging performance test results of the polyethylene composite materials prepared in Example 2 of the present invention and Comparative Examples 1 to 5. DETAILED DESCRIPTION
[0016] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. It should be noted that, unless otherwise specified, the raw materials involved in the present invention are purchased through conventional commercial channels.
[0017] Embodiment 1: A polyethylene composite material, comprising the following components in parts by weight: 60 parts of high-density polyethylene, 0.6 parts of maleic anhydride, 6 parts of polyolefin elastomer, 3 parts of polypropylene microfiber, 4 parts of modified glass fiber, 2 parts of silane-modified montmorillonite, 1 part of nano-silica, 0.6 parts of zinc stearate, 0.5 parts of polyethylene wax, 0.2 parts of primary antioxidant and 0.2 parts of auxiliary antioxidant.
[0018] High-density polyethylene is prepared by washing, drying, crushing and drying recycled laundry detergent bottles; The specific preparation steps of silane-modified montmorillonite are as follows: A1: 10g of montmorillonite was added to 150mL of deionized water, and the mixture was dispersed evenly by ultrasonic treatment to obtain a montmorillonite dispersion; 2g of hexadecyltrimethylammonium bromide was added to 200mL of deionized water, and the mixture was stirred to obtain a 1wt% active agent solution; 4g of γ-aminopropyltriethoxysilane was added to 100mL of 90wt% ethanol solution, and the mixture was stirred to obtain a 4wt% silanol solution; the pH value was adjusted to 5 with 0.1M hydrochloric acid solution, and the mixture was hydrolyzed at room temperature for 30min to obtain a 4wt% silanol solution; A2: Slowly add 150 mL of the active agent solution prepared in step A1 to 150 mL of montmorillonite dispersion, control the temperature at 60°C, stir and react for 6 hours, wash with deionized water, and dry at 60°C for 12 hours to obtain organic montmorillonite; add 10 g of organic montmorillonite to 60 mL of the silanol solution prepared in step A1, stir and react at 50°C for 4 hours, wash with deionized water, and vacuum dry at 80°C for 12 hours to obtain silane-modified montmorillonite; The specific preparation steps of modified glass fiber are as follows: B1: The glass fiber was completely immersed in deionized water, ultrasonically treated at 100W for 15 minutes, filtered, and dried at 60°C for 6 hours to obtain pretreated glass fiber; 10g of pretreated glass fiber was added to 50mL of concentrated nitric acid, stirred and reacted at room temperature for 2 hours. After the reaction was completed, it was washed with deionized water until neutral to obtain neutral glass fiber; B2: 10 g of the neutral glass fiber prepared in step B1 was added to 50 mL of 70 wt% ethanol solution, soaked for 30 min, then washed with deionized water for 3 times, and vacuum dried at 80 ° C for 12 h to obtain modified glass fiber; The specific preparation steps of the polyethylene composite material are as follows: S1: Wash high-density polyethylene with deionized water and vacuum dry it at 80°C for 12 hours to obtain pretreated high-density polyethylene; stir and mix the pretreated high-density polyethylene, polyolefin elastomer, zinc stearate, polyethylene wax, butylated hydroxytoluene and didothiodipropionate to obtain a pretreated mixture; ultrasonically treat silane-modified montmorillonite, nano-silica and modified glass fiber and pre-disperse them in deionized water; extrude polypropylene at 200°C and stretch it at the same time, with a stretch ratio parameter of 15, to form 2 mm polypropylene microfibers; S2: adding the pretreated mixture prepared in step S1 into the extruder, melt blending at 190°C, controlling the speed at 60rpm, and the time for 3min, then slowly adding maleic anhydride, raising the temperature to 200°C, reacting for 5min, and performing the first exhaust, the exhaust pressure is -0.08MPa, and the time is 5min; S3: After completing the operation in step S2, the silane-modified montmorillonite, nano-silica and modified glass fiber after ultrasonic dispersion in step S1 are added in sequence, the extrusion temperature is increased to 220° C., the rotation speed is increased to 80 rpm, and the mixing time is 8 min; S4: After completing the operation in step S3, slowly add the polypropylene microfiber prepared in step S1, reduce the rotation speed to 50rpm, reduce the temperature to 200℃ at a rate of 5℃ / min, and disperse for 5min. After dispersion, reduce the temperature to 190℃ at a rate of 2℃ / min, perform the second exhaust with an exhaust pressure of -0.08MPa for 5min, extrude, and then cool the extrudate to room temperature, first cool it with 40℃ water for 2min, and then naturally cool it to room temperature to obtain a polyethylene composite material.
[0019] Example 2: A polyethylene composite material, comprising the following components in parts by weight: 65 parts of high-density polyethylene, 1 part of maleic anhydride, 10 parts of polyolefin elastomer, 5 parts of polypropylene microfibers, 6 parts of modified glass fibers, 3 parts of silane-modified montmorillonite, 2 parts of nano-silica, 1 part of zinc stearate, 1 part of polyethylene wax, 0.3 parts of a primary antioxidant and 0.3 parts of an auxiliary antioxidant.
[0020] High-density polyethylene is prepared by washing, drying, crushing and drying recycled laundry detergent bottles; The specific preparation steps of silane-modified montmorillonite are as follows: A1: 10g of montmorillonite was added to 200mL of deionized water, and the mixture was dispersed evenly by ultrasonic treatment to obtain a montmorillonite dispersion; 6g of hexadecyltrimethylammonium bromide was added to 300mL of deionized water, and the mixture was stirred to obtain a 2wt% active agent solution; 4g of γ-aminopropyltriethoxysilane was added to 100mL of 90wt% ethanol solution, and the mixture was stirred to obtain a 4wt% silanol solution; the pH value was adjusted to 4 with 0.1M hydrochloric acid solution, and the mixture was hydrolyzed at room temperature for 30min to obtain a 4wt% silanol solution; A2: Slowly add 300 mL of the active agent solution prepared in step A1 to 200 mL of montmorillonite dispersion, control the temperature to 70°C, stir and react for 4 hours, wash with deionized water, and dry at 60°C for 24 hours to obtain organic montmorillonite; add 10 g of organic montmorillonite to 80 mL of the silanol solution prepared in step A1, stir and react at 60°C for 2 hours, wash with deionized water, and vacuum dry at 80°C for 12 hours to obtain silane-modified montmorillonite; The specific preparation steps of modified glass fiber are as follows: B1: The glass fiber was completely immersed in deionized water, ultrasonically treated at 100W for 15 minutes, filtered, and dried at 60°C for 6 hours to obtain pretreated glass fiber; 10g of pretreated glass fiber was added to 60mL of concentrated nitric acid, stirred and reacted at room temperature for 4 hours. After the reaction was completed, it was washed with deionized water until neutral to obtain neutral glass fiber; B2: 10 g of the neutral glass fiber prepared in step B1 was added to 100 mL of 70 wt% ethanol solution, soaked for 30 min, then washed with deionized water for 3 times, and vacuum dried at 80 ° C for 24 h to obtain modified glass fiber; The specific preparation steps of the polyethylene composite material are as follows: S1: high-density polyethylene was washed with deionized water and vacuum dried at 80°C for 12 hours to obtain pretreated high-density polyethylene; pretreated high-density polyethylene, polyolefin elastomer, zinc stearate, polyethylene wax, 2,4-di-tert-butylphenol and tri(nonylphenyl)phosphite were stirred and mixed to obtain a pretreated mixture; silane-modified montmorillonite, nano-silica and modified glass fiber were ultrasonically treated and pre-dispersed in deionized water respectively; polypropylene was extruded at 200°C and stretched at the same time, with a stretching ratio parameter of 20 to form 3 mm polypropylene microfibers; S2: adding the pretreated mixture prepared in step S1 into the extruder, melt blending at 200°C, controlling the speed at 60rpm, and the time for 5min, then slowly adding maleic anhydride, raising the temperature to 210°C, reacting for 10min, and performing the first exhaust, the exhaust pressure is -0.08MPa, and the time is 8min; S3: After completing the operation in step S2, the silane-modified montmorillonite, nano-silica and modified glass fiber after ultrasonic dispersion in step S1 are added in sequence, the extrusion temperature is increased to 220° C., the rotation speed is increased to 80 rpm, and the mixing time is 10 min; S4: After completing the operation in step S3, slowly add the polypropylene microfiber prepared in step S1, reduce the rotation speed to 70rpm, reduce the temperature to 200℃ at a rate of 5℃ / min, and disperse for 6min. After dispersion, reduce the temperature to 190℃ at a rate of 2℃ / min, perform the second exhaust with an exhaust pressure of -0.08MPa for 8min, extrude, and then cool the extrudate to room temperature, first cool it with 40℃ water for 3min, and then naturally cool it to room temperature to obtain a polyethylene composite material.
[0021] Example 3: A polyethylene composite material, comprising the following components in parts by weight: 70 parts of high-density polyethylene, 0.8 parts of maleic anhydride, 8 parts of polyolefin elastomer, 4 parts of polypropylene microfibers, 5 parts of modified glass fibers, 2.5 parts of silane-modified montmorillonite, 1.5 parts of nano-silica, 0.8 parts of zinc stearate, 0.8 parts of polyethylene wax, 0.25 parts of a primary antioxidant and 0.25 parts of an auxiliary antioxidant.
[0022] High-density polyethylene is prepared by washing, drying, crushing and drying recycled laundry detergent bottles; The specific preparation steps of silane-modified montmorillonite are as follows: A1: 10g of montmorillonite was added to 180mL of deionized water, and the mixture was dispersed evenly by ultrasonic treatment to obtain a montmorillonite dispersion; 4.5g of hexadecyltrimethylammonium bromide was added to 300mL of deionized water, and the mixture was stirred to obtain a 1.5wt% active agent solution; 4g of γ-aminopropyltriethoxysilane was added to 100mL of 90wt% ethanol solution, and the mixture was stirred to obtain a 4wt% silanol solution; the pH value was adjusted to 4.5 with 0.1M hydrochloric acid solution, and the mixture was hydrolyzed at room temperature for 30min to obtain a 4wt% silanol solution; A2: Slowly add 250 mL of the active agent solution prepared in step A1 to 180 mL of montmorillonite dispersion, control the temperature at 65°C, stir and react for 5 hours, wash with deionized water, and dry at 60°C for 18 hours to obtain organic montmorillonite; add 10 g of organic montmorillonite to 70 mL of the silanol solution prepared in step A1, stir and react at 55°C for 3 hours, wash with deionized water, and vacuum dry at 80°C for 12 hours to obtain silane-modified montmorillonite; The specific preparation steps of modified glass fiber are as follows: B1: The glass fiber was completely immersed in deionized water, ultrasonically treated at 100W for 15 minutes, filtered, and dried at 60°C for 6 hours to obtain pretreated glass fiber; 10g of pretreated glass fiber was added to 55mL of concentrated nitric acid, stirred and reacted at room temperature for 3 hours. After the reaction was completed, it was washed with deionized water until neutral to obtain neutral glass fiber; B2: 10 g of the neutral glass fiber prepared in step B1 was added to 80 mL of 70 wt% ethanol solution, soaked for 30 min, then washed with deionized water for 3 times, and vacuum dried at 80 ° C for 18 h to obtain modified glass fiber; The specific preparation steps of the polyethylene composite material are as follows: S1: Wash high-density polyethylene with deionized water, and vacuum dry it at 80°C for 12 hours to obtain pretreated high-density polyethylene; stir and mix the pretreated high-density polyethylene, polyolefin elastomer, zinc stearate, polyethylene wax, 2,6-di-tert-butyl-p-cresol and diphenyl phosphite to obtain a pretreated mixture; ultrasonically treat silane-modified montmorillonite, nano-silica and modified glass fiber and pre-disperse them in deionized water; extrude polypropylene at 200°C and stretch it at the same time, with a stretch ratio parameter of 18, to form 2.5 mm polypropylene microfibers; S2: adding the pretreated mixture prepared in step S1 into an extruder, melt blending at 195°C, controlling the speed at 60 rpm, and reacting for 4 min, then slowly adding maleic anhydride, raising the temperature to 205°C, reacting for 8 min, and performing the first exhaust, with an exhaust pressure of -0.08 MPa, and reacting for 6 min; S3: After completing the operation in step S2, the silane-modified montmorillonite, nano-silica and modified glass fiber after ultrasonic dispersion in step S1 are added in sequence, the extrusion temperature is increased to 220° C., the rotation speed is increased to 80 rpm, and the mixing time is 9 min; S4: After completing the operation in step S3, slowly add the polypropylene microfiber prepared in step S1, reduce the rotation speed to 60rpm, reduce the temperature to 200℃ at a rate of 5℃ / min, and disperse for 5.5min. After dispersion, reduce the temperature to 190℃ at a rate of 2℃ / min, perform the second exhaust with an exhaust pressure of -0.08MPa for 6min, extrude, and then cool the extrudate to room temperature, first cool it with 40℃ water for 2.5min, and then naturally cool it to room temperature to obtain a polyethylene composite material.
[0023] Comparative Example 1: The operation of Comparative Example 1 is substantially the same as that of Example 2, except that maleic anhydride is not added in Comparative Example 1.
[0024] Comparative Example 2: The operation of Comparative Example 2 is substantially the same as that of Example 2, except that polypropylene microfiber is not added in Comparative Example 2.
[0025] Comparative Example 3: The operation of Comparative Example 3 is basically the same as that of Example 2, except that silane-modified montmorillonite and nano-silica are not added in Comparative Example 3.
[0026] Comparative Example 4: The operation of Comparative Example 4 is substantially the same as that of Example 2, except that no polyolefin elastomer is added in Comparative Example 4.
[0027] Comparative Example 5: The operation of Comparative Example 5 is substantially the same as that of Example 2, except that in Comparative Example 5, the polypropylene microfiber is not added in stages, but is added and mixed with the glass fiber simultaneously.
[0028] Performance Test: Mechanical strength test: The tensile strength and flexural strength tests of the polyethylene composite samples prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were performed using a universal material testing machine RH-5000. The tensile strength was tested in accordance with GB / T 1040.1-2018; the flexural strength was tested in accordance with GB / T 9341-2008; the impact strength and absorbed energy were tested using a plastic pendulum impact tester in accordance with GB / T 1843-2008. The results of tensile strength, flexural strength and impact strength are shown in Table 1 below; the test results of impact strength and absorbed energy comparison are shown in Table 2. Figure 1 shown.
[0029] Table 1. Mechanical strength test results of polyethylene composites
[0030] From Table 1 and Figure 1The results show that the polyethylene composite material prepared by the present invention has good tensile strength, flexural strength and impact strength, and has excellent mechanical properties; from the results of Comparative Example 1 and Example 2, it can be seen that the grafting modification effect of maleic anhydride is missing, the compatibility of the inorganic filler and the HDPE matrix is significantly affected, the interface bonding force is significantly reduced, and the embedding effect of the glass fiber and the matrix may also be weakened, which leads to a significant decrease in the overall strength; from the results of Comparative Example 2 and Example 2, it can be seen that the polypropylene microfibers that are stretched into fibers are missing, the matrix lacks an important reinforcing phase, the load-bearing capacity at break is weakened, and the interference effect on the crack propagation path disappears, and the material's ability to absorb dynamic loads is significantly reduced; from the results of Comparative Example 3 and Example 2, It can be seen from the results that after the loss of montmorillonite and nano-SiO2, the composite material loses the support of nano-reinforcement and multi-level structure, the cracks are easy to expand, the tensile strength and bending properties are greatly weakened, in addition, the crack resistance and local stress dispersion effects of the inorganic filler are lost, the cracks expand more rapidly, and the material is more likely to break; from the results of Comparative Example 4 and Example 2, it can be seen that the toughening effect of the polyolefin elastomer is lacking, the energy absorption capacity under dynamic load is significantly reduced, and the impact strength of the material is significantly reduced; from the results of Comparative Example 5 and Example 2, it can be seen that the polypropylene microfibers and glass fibers are added at the same time, and the dispersion is uneven, which may lead to a weakening of the reinforcement effect, and the simultaneous addition of the polypropylene microfibers may lead to local agglomeration, which in turn leads to a significant decrease in the toughness effect.
[0031] Thermal performance test: The polyethylene composite materials prepared in Example 2 and Comparative Examples 1 to 5 were placed in a thermogravimetric analyzer, the heating rate was set to 10°C / min, the temperature was increased to 600°C, the initial decomposition temperature (Tonset) and the maximum decomposition rate temperature (Tmax) of the material were recorded, and the percentage of the remaining mass of the sample at high temperature was recorded at the same time. The results are shown in Table 2 below.
[0032] Table 2. Thermal properties test results of polyethylene composites
[0033] It can be seen from the results in Table 2 that the polyethylene composite material prepared by the present invention has a higher initial decomposition temperature and a maximum decomposition rate temperature, and the residual mass percentage is also large, indicating that its inorganic filler is effectively dispersed and uniform, the interface bonding force is strong, and the overall thermal stability of the material is good; from the results of Comparative Example 1 and Example 2, it can be seen that the lack of maleic anhydride grafting modification, the interface bonding force is poor, the dispersibility of the inorganic filler is reduced, and the thermal stability of the filler may not be fully exerted, which leads to a significant impact on the thermal decomposition performance; from the results of Comparative Example 2 and Example 2, it can be seen that the lack of polypropylene microfiber reinforcement, the effect of the crystal structure of the microfiber on the thermal stability is lost, and the thermal stability is affected to a certain extent; from the results of Comparative Example 3 and Example 2, it can be seen that the barrier effect of the nanofiller is lacking, which may cause the volatile components to migrate more easily, the high temperature support effect of montmorillonite and nano-silica is lacking, the overall thermal stability of the material is reduced, and at the same time, due to the reduction in filler mass, the residual inorganic components are significantly reduced; from the results of Comparative Example 5 and Example 2, it can be seen that the polypropylene microfibers are unevenly dispersed, the matrix and the fiber interface bonding force is weakened, and the thermal stability is affected to a certain extent.
[0034] Anti-aging test: The polyethylene composite material samples prepared in Example 2 and Comparative Examples 1 to 5 were subjected to UV lamp aging test, and the test parameters were UVA-340 lamp tube simulating ultraviolet rays (0.35 W / m 2 ), temperature 60℃, humidity 75%, photoperiod of 12h light, 12h dark, test for 800h, record the percentage change of tensile strength of the sample at 96h, 240h, 500h and 800h (tensile strength change = (tensile strength before test - tensile strength after test) / tensile strength before test × 100%), the results are as follows Figure 2 shown.
[0035] Depend on Figure 2 As can be seen from the results, the polyethylene composite material prepared by the present invention has good anti-aging performance and can be effectively used for a long time under outdoor exposure conditions; from the results of Comparative Example 1 and Example 2, it can be seen that the lack of maleic anhydride leads to poor interface bonding between the filler and the matrix, and the filler may fall off after aging, resulting in performance being affected; from the results of Comparative Example 2 and Example 2, it can be seen that the lack of polypropylene microfiber effect, the anti-crack and degradation delay effects of microfiber distribution disappear, which may lead to obvious aging; from the results of Comparative Example 3 and Example 2, it can be seen that the lack of UV blocking effect of modified montmorillonite and nano-silica may lead to aggravated photo-oxidative degradation and significantly affected mechanical properties; from the results of Comparative Example 4 and Example 2, it can be seen that the lack of toughening of polyolefin elastomer, the crack extension is aggravated after aging, the UV blocking and antioxidant effects of the remaining fillers are still there, and the overall decline is small; from the results of Comparative Example 5 and Example 2, it can be seen that the polypropylene microfibers are unevenly dispersed, the microfiber reinforced network effect is weakened, the aging resistance is affected to a certain extent, and the mechanical strength is reduced.
[0036] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A polyethylene composite material, characterized in that: The composition includes the following components in parts by weight: 60-70 parts of high-density polyethylene, 0.6-1 parts of maleic anhydride, 6-10 parts of polyolefin elastomer, 3-5 parts of polypropylene microfiber, 4-6 parts of modified glass fiber, 2-3 parts of silane-modified montmorillonite, 1-2 parts of nano silicon dioxide, 0.6-1 parts of zinc stearate, 0.5-1 parts of polyethylene wax, 0.2-0.3 parts of primary antioxidant and 0.2-0.3 parts of auxiliary antioxidant.
2. A polyethylene composite material according to claim 1, characterized in that: The primary antioxidant is any one of butylated hydroxytoluene, 2,4-di-tert-butylphenol and 2,6-di-tert-butyl-p-cresol.
3. A polyethylene composite material according to claim 2, characterized in that: The auxiliary antioxidant is any one of didodecanedipropionate, tris(nonylphenyl)phosphite and diphenylphosphite.
4. A polyethylene composite material according to claim 3, characterized in that: The specific preparation steps of the silane-modified montmorillonite are as follows: A1: Add montmorillonite to deionized water, disperse evenly by ultrasonic treatment, and obtain a montmorillonite dispersion; add hexadecyltrimethylammonium bromide to deionized water, stir and mix evenly, and obtain a 1-2wt% active agent solution; add γ-aminopropyltriethoxysilane to the ethanol solution, stir and mix evenly, adjust the pH to 4-5 with 0.1M hydrochloric acid solution, and hydrolyze at room temperature to obtain a 4wt% silanol solution; A2: slowly add the active agent solution prepared in step A1 to the montmorillonite dispersion, control the temperature at 60-70°C, stir to react, wash with deionized water, and dry to obtain organic montmorillonite; add the organic montmorillonite to the silanol solution prepared in step A1, stir to react, wash with deionized water, and vacuum dry to obtain silane-modified montmorillonite.
5. A polyethylene composite material according to claim 4, characterized in that: In step A1, the ratio of the amount of montmorillonite to deionized water is 1 g: 15-20 mL; in step A2, the volume ratio of the active agent solution to the montmorillonite dispersion is 1-1.5:1; and the ratio of the amount of the organic montmorillonite to the silanol solution is 1 g: 6-8 mL.
6. A polyethylene composite material according to claim 5, characterized in that: The specific preparation steps of the modified glass fiber are as follows: B1: The glass fiber is completely immersed in deionized water, subjected to ultrasonic treatment, filtered, and dried to obtain pretreated glass fiber; the pretreated glass fiber is added to concentrated nitric acid, stirred and reacted at room temperature, and after the reaction is completed, washed with deionized water until neutral to obtain neutral glass fiber; B2: The neutral glass fiber prepared in step B1 is added to an ethanol solution, soaked, then repeatedly washed with deionized water, and vacuum dried to obtain a modified glass fiber.
7. A polyethylene composite material according to claim 6, characterized in that: In step B1, the ratio of the amount of the pretreated glass fiber to the concentrated nitric acid is 1 g: 5-6 mL; in step B2, the ratio of the amount of the neutral glass fiber to the ethanol solution is 1 g: 5-10 mL.
8. A method for preparing the polyethylene composite material according to any one of claims 1 to 7, characterized in that: The specific preparation steps are as follows: S1: washing high-density polyethylene with deionized water and vacuum drying to obtain pretreated high-density polyethylene; stirring and mixing the pretreated high-density polyethylene, polyolefin elastomer, zinc stearate, polyethylene wax, primary antioxidant and auxiliary antioxidant to obtain a pretreated mixture; pre-dispersing silane-modified montmorillonite, nano-silica and modified glass fiber in deionized water by ultrasonic treatment respectively; extruding polypropylene through an extruder and stretching it at the same time to form polypropylene microfibers; S2: adding the pretreated mixture prepared in step S1 into an extruder, melt blending at 190-200° C., controlling the speed to 60 rpm, mixing time 3-5 min, then slowly adding maleic anhydride, raising the temperature to 200-210° C., and reacting for 5-10 min; S3: After completing the operation in step S2, add the silane-modified montmorillonite, nano-silica and modified glass fiber after ultrasonic dispersion in step S1 in sequence, increase the extrusion temperature to 220° C., increase the rotation speed, and mix for 8 to 10 minutes; S4: After completing the operation in step S3, slowly add the polypropylene microfibers prepared in step S1, reduce the rotation speed, reduce the temperature to 200°C at a rate of 5°C / min, and disperse for 5 to 6 minutes. After dispersion, reduce the temperature to 190°C at a rate of 2°C / min, extrude, and then cool the extrudate to room temperature to obtain a polyethylene composite material.
9. A method for preparing the polyethylene composite material according to claim 8, characterized in that: In step S1, the stretching parameter of the polypropylene is a stretching ratio of 15 to 20; in step S2, after the maleic anhydride grafting reaction is completed, the first exhaust is performed, the exhaust pressure is -0.08 MPa, and the time is 5 to 8 minutes.
10. A method for preparing the polyethylene composite material according to claim 9, characterized in that: In step S4, after the polypropylene microfibers are added and mixed, a second exhaust is performed with an exhaust pressure of -0.08 MPa for 5 to 8 minutes; the extrudate cooling step is firstly cooling with 40° C. water for 2 to 3 minutes, and then naturally cooling to room temperature.
Citation Information
Patent Citations
Insulating heat-conducting cable material and preparation method thereof
CN108727670A
High-barrier puncture-resistant polyethylene composite film as well as preparation method and application thereof
CN118700596A
Nanocomposite Packaging Film
US20160347919A1
Cited By
High-strength waterproof polyethylene composite material and preparation method thereof
CN119978593A
Impact-resistant HDPE corrugated pipe and preparation method thereof
CN120209440A
Impact-resistant HDPE corrugated pipe and preparation method thereof
CN120209440B
High-barrier modified polyethylene
CN120248481A
Water-resisting and salt-resisting composite geomembrane and preparation method thereof
CN120269904A